Peningkatan Hasil Belajar Mata Pelajaran SKI Melalui Penerapan Strategi Question Students Have: Penelitian Tindakan pada Siswa Kelas VIII MTSN 2 Lombok Timur - Supriadin Supriadin (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2022)
The use of the Question Students Have strategy in the Subject of Islamic Cultural History is one of the efforts to improve the quality of education, especially to increase student learning outcomes. This is done because there is still low educational interaction in the classroom when learning takes place. Hence, students tend to be passive and lack the courage to express opinions or ask questions, which has implications for the achievement of students' daily assessment results below the KKM standard. This study aims to improve student learning outcomes in class VIII-D in SKI subjects by applying the Question Students Have learning strategy. This research was conducted on students of class VIII-D Negeri 2 East Lombok totalling 30 students. This research is action research with two cycles through 4 stages; planning, action, observation, and reflection. The results showed that student learning outcomes increased after learning action was carried out using the Question Students Have learning strategy. The results of the analysis are presented as follows. In cycle I, students only achieved an average score of 72.33, with a classical completeness percentage of 66.67% of all students. In cycle II the average student learning outcomes were 77.27, with a classical completeness percentage of 90%. That means that students' learning completeness classically increased by 29.97% from cycle I and 56.99% compared to the pre-test scores before the action. Keywords: Learning Outcomes; skiing; Question Students Have Abstrak: Penggunaan strategi Question Students Have pada Mata Pelajaran Sejarah Kebudayaan Islam merupakan salah satu upaya untuk meningkatkan mutu pendidikan, khususnya untuk meningkatkan hasil belajar siswa. Hal ini dilakukan karena masih rendahnya interaksi edukatif di dalam kelas saat pembelajaran berlangsung. Sehingga, siswa cenderung pasif dan kurang berani mengemukakan pendapat atau bertanya, yang berimplikasi pada pencapaian hasil penilaian harian siswa di bawah standar KKM. Penelitian ini bertujuan meningkatkan hasil belajar siswa kelas VIII-D pada mata pelajaran SKI dengan penerapan strategi pembelajaran Question Students Have. Penelitian ini dilakukan terhadap siswa kelas VIII-D Negeri 2 Lombok Timur berjumlah 30 orang siswa. Penelitian ini merupakan penelitian tindakan dengan 2 siklus melalui 4 tahapan; perencanaan, tindakan, pengamatan, dan refleksi. Hasil penelitian menunjukkan bahwa hasil belajar siswa mengalami peningkatan setelah dilakukan tindakan pembelajaran dengan Strategi pembelajaram Question Students Have. Hasil analisis dikemukakan sebagai berikut. Siklus I, siswa hanya mencapai nilai rat-rata 72,33 dengan persentase ketuntasan klasikal sebesar 66,67% dari keseluruhan siswa. Pada siklus II hasil belajar rata-rata siswa 77,27 dengan persentase ketuntasan klasikal sebesar 90%. Hal ini berarti ketuntasan belajar siswa secara klasikal meningkat 29,97% dari siklus I, dan meningkat 56, 99% dibandingkan dengan nilai pre test sebelum tindakan.